2016
DOI: 10.3892/ijo.2016.3750
|View full text |Cite
|
Sign up to set email alerts
|

IMP-3 protects the mRNAs of cyclins D1 and D3 from GW182/AGO2-dependent translational repression

Abstract: IGF-2 mRNA binding protein 3 (IGF2BP3, IMP-3) is a well-known post-transcriptional regulatory factor of gene expression, mainly involved in embryonic development and oncogenesis. We have previously demonstrated that a subset of IMP-3 targets, such as the mRNAs of cyclins D1, D3 and G1, are positively regulated by IMP-3, and that this regulation depends on nuclear localization of IMP-3. In the present study, we show that as a first step following a knock-down of IMP-3, the protein levels of the cyclins rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…While investigating the role of DDX5 in cell cycle regulation in spermatogonia, we identified and confirmed interaction of DDX5 with ILF3 and its protein partners ILF2 and IGF2BP3 57,58 (Fig. 4b and Supplementary Data 3).…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…While investigating the role of DDX5 in cell cycle regulation in spermatogonia, we identified and confirmed interaction of DDX5 with ILF3 and its protein partners ILF2 and IGF2BP3 57,58 (Fig. 4b and Supplementary Data 3).…”
Section: Resultsmentioning
confidence: 54%
“…6b). Previous studies have demonstrated that ILF3 is involved in post-transcriptional regulation of cyclin mRNAs 57,62 . Therefore, we performed ILF3 RIP-qPCR experiments in cultured wildtype spermatogonia to identify cyclin mRNAs bound to ILF3 and elucidate a potential co-regulatory role with DDX5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, IMP3 is a crucial transcriptional regulator, which binds a couple of mRNAs and modulates their expressions 2022. IMP-3 binds to and positively regulates the expressions of cyclins D1, D3 and G1 in a number of human cancer cell lines 20,21. IMP3 also binds avidly to SNAI2 mRNA and regulates its expression by binding to the 5‘ UTR 22.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, analysis of LINC01420 RNA-binding proteins revealed that many of them are involved in regulation of mRNA nuclear export, translation and stability (e.g. EIF4A3 [44], IGF2BP1 [45], IGF2BP2 [46], IGF2BP3 [47], UPF1 [48]). It indicates the protein coding function of this transcript.…”
Section: Discussionmentioning
confidence: 99%